Assessing Public Perception of Self-Driving Cars: the Autonomous Vehicle Acceptance Model - Hewitt, Charlie; Politis, Ioannis; Amanatidis, Theocharis; Sarkar, Advait (24th International Conference on Intelligent User interfaces (IUI 2019), 2019)
We introduce the Autonomous Vehicle Acceptance Model (AVAM), a model of user acceptance for autonomous vehicles, adapted from existing models of user acceptance for generic technologies. A 26-item questionnaire is developed in accordance with the model and a survey conducted to evaluate 6 autonomy scenarios. In a pilot survey (n=54) and follow-up survey (n=187), the AVAM presented good internal consistency and replicated patterns from previous surveys. Results showed that users were less accepting of high autonomy levels and displayed significantly lower intention to use highly autonomous vehicles. We also assess expected driving engagement of hands, feet and eyes which are shown to be lower for full autonomy compared with all other autonomy levels. This highlighted that partial autonomy, regardless of level, is perceived to require uniformly higher driver engagement than full autonomy. These results can inform experts regarding public perception of autonomy across SAE levels. The AVAM and associated questionnaire enable standardised evaluation of AVs across studies, allowing for meaningful assessment of changes in perception overtime and between different technologies.